The Construction of Tissue‐Engineered Blood Vessels Crosslinked with Adenosine‐Loaded Chitosan/β‐Cyclodextrin Nanoparticles using a Layer‐by‐Layer Assembly Method. Issue 11 (20th June 2014) - Chen, Wen; Zeng, Wen; Wu, Yangxiao; Wen, Can; Li, Li; Liu, Ge; Shen, Lei; Yang, Mingcan; Tan, Ju; Zhu, Chuhong
<x xml:space="preserve">Abstract</x> A tissue‐engineered blood vessel (TEBV) modified with CS/β‐CD nanoparticles is constructed, effectively controling the release of adenosine, and this type of TEBV can keep open for over 6 months. This study also demonstrates for the first time that adenosine promotes endothelial progenitor cell (EPC) mobilization and homing via energy conversion, achieving rapid endothelialization of TEBV. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>